PENGEMBANGAN MODEL MOTIVASI JUMANIOR (JURU PEMANTAU JENTIK JUNIOR) DALAM PERILAKU PSN (PEMBERANTASAN SARANG NYAMUK) AEDES AEGEPTY BERBASIS INTEGRASI MODEL LAWRANCE GREEN DAN Mc. CLELLEAND - Afrian, Nian; Widayati, Dhina; Setyorini, Dwi (Unusa Press, 2016)
Dengue fever is a disease in humans caused by a virus that infects an estimated 50 million people in the tropics and sub-tropics every year. Aedes aegypti is the main vector of the disease that has a high adaptability to cans in breeding. Various attempts have been made to reduce the incidence of this disease, including PSN (mosquito nest elimination), fumigation, and abatisasi but in fact until now the incidence of dengue fever is still quite high. The purpose of this study to determine the relationship of knowledge and attitude with motivation of Jumanior to elimination nest mosquito in SD NU and Nurul Islam Pare. This research method using correlational design with cross sectional study. The sample in this study is Jumanior (elementary school students as larva monitoring juniors) of 40 people obtained by purposive sampling. The dependent variable are the knowledge and attitudes, independent variable is Jumanior’s motivation measured in the implementation of PSN by questionnaire. Data analized with a statistical test Chi Square. The results showed relationship between the level of knowledge and motivation with strong relationships and a positive direction (cc= 0.733 and p-value = 0.002) and relationship between attitude and motivation with the power relationships in a strong category, positive direction, (cc = 0.724 and p value = 0.014). Jumanior with good knowledge about the prevention of dengue fever will affect the attitude which will lead to Jumanior in implementing PSN. PSN should be included in the material in UKS or extracurricular engaged in the health sector, so that it can be a medium of information for students who play an important role in this regard as change agent in the home environment and health to maintain a healthy school environment.